REAL TEACHING: ANXIETY AND SOLUTION - Vina Agustiana (English Review: Journal of English Education, 2019)
Anxiety in dealing with real teaching is experienced by preservice teachers. This anxiety can certainly disrupt the process of implementing real teaching. If anxiety can be detected early, various efforts can be made to reduce the anxiety. Thus, this study seeks to explore the anxiety faced by preservice teacher in dealing with real teaching and their efforts to reduce such anxiety. In order to achieve the research objectives, the researcher applied qualitative research through a case study strategy using structured interviews of 238 preservice teachers at one of Indonesia’s private universities. Based on the results of the study, it can be seen that there are 14 anxiety faced by preservice teachers in carrying out real teaching which is divided into 5 factors causing anxiety, namely schools, teachers, students, lecturers, and the preservice teachers themselves, as well as 9 attempts by preservice teachers in order to deal with this anxiety. Broadly speaking, good communication between preservice teachers and stakeholders of real teaching activities that includes schools, teachers, students, and lecturers is an effort that can be done so that the teaching anxiety can be reduced.